A reader on punishment - Duff, Antony; Garland, David (Oxford readings in socio-legal studies, 1997)
Why we punish, who we punish and how we punish are central elements of any discussion of the role of law in modern society. In this impressive and timely collection, two leading experts on the theory of punishment have selected a range of articles which have made important and influential contributions to the ways in which punishment is understood in contemporary society. The collection is introduced by a lengthy and original discussion of the key concepts of punishment, and each article is prefaced by a short introduction setting out the issues to be discussed. Throughout the book the aim of the editors is to demonstrate how complex the concept of punishment is, and to illustrate how an understanding of punishment is vitally important for students of law and society.